Analisis Organoleptik Ikan Julung-Julung (Hemirhampus far) Asap Cair dengan Perlakuan Lama Perendaman Berbeda - Patra, Fitriani; Sulistijowati, Rieny; Mile, Lukman (The NIKe Journal, 2023)
This research aims to determine the organoleptic value of julung-julung fish (Hemirhampus far) with 3% concentration of liquid smoke treated with different soaking times (25, 30 and 35 minutes). This research was carried out in April - September 2016 at the Biotechnology and Fishery Product Characteristics Laboratory, Faculty of Fisheries and Marine Sciences, Gorontalo State University for Organoleptic testing. Data analysis used for organoleptic testing of hedonic quality was Kruskal Wallis followed by Duncan's advanced test. Organoleptic test results for the hedonic quality of julung-julung fish (Hemirhampus far) from liquid smoke with different soaking times produced different organoleptic values for all parameters. Based on the results of the organoleptic test, the soaking time of 30 minutes and 35 minutes is different from the soaking time of 25 minutes, namely having an average value of 7 for the appearance parameters which are in the criteria of intact, clean, brown, shiny, specific to the type; the smell is in the criteria of less fragrant, sufficient smoke, without additional disturbing odors; The taste is in the criteria of good but not tasty, while in terms of texture parameters, the soaking time of 25 minutes and 30 minutes is different from the soaking time of 35 minutes, namely with an average value of 7 which is in the criteria of solid, compact, quite dry and tight tissue.